IMPLEMENTATION OF EXTENSIVE READING THROUGH A DIGITAL INSTRUCTIONAL MEDIA - vina Nurviyani (STKIP Siliwangi, 2020)
This study explored the implementation of extensive reading through a digital instructional media. In this case, it was Padlet. Moreover, the students’ difficulties in conducting the extensive reading through Padlet was investigated. The extensive reading implemented in this research referred to the ten principles of the extensive reading programme proposed by Day and Bamford (2002). This research was conducted at a private university in West Java by applying a case study and involving thirty college students. Moreover, observations and questionnaire were used as data collection techniques. The findings show that students are excited during the extensive reading processes by using their smart phones because they are allowed to select reading material freely. During the extensive reading process, they practiced recalling the text they had read by using Padlet application. Having implementing the extensive reading through Padlet, they feel that extensive reading has made them accustomed to reading everyday subconsciously. Thus, they are able to comprehend the reading material more easily. It can be seen from their developement in stating the generic structure of certain genre in the recall session. However, some students got troubles during the extensive reading processes, such as less capablity of digital literacy and low motivation.